Former Yugoslav National parks are going social? An exploratory study on Facebook - Dragović, Nataša; Cimbaljević, Marija; Stankov, Uglješa; Vasiljević, Đorđije; Vujičić, Miroslav; Pavluković, Vanja (Turizam, 2018)
Today, a large number of people use the Internet for a variety of purposes. There is a growing presence of social networks in different spheres of life. Consequently, the connection of national parks and social media has begun. In this way, the management of national parks is facilitated in general, because data from social media can be of great help. Communication with visitors of national parks, through social media, has great potential in protecting such areas, but also in providing a wealth of experience. Therefore, it is essential to constantly update and direct visitors to the official Facebook sites of national parks. In this paper, the presence and activity of national parks sites on Facebook, in Former Yugoslavia (Bosnia and Herzegovina, Croatia, FYR Macedonia, Montenegro, Serbia and Slovenia) is explored with the aim to seek for common practices, good examples or pitfalls.